2014
DOI: 10.3109/07357907.2014.988340
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of CD40/CD40L On XG1 Multiple Myeloma Cells Promotes IL-6 Autocrine Function

Abstract: Multiple myeloma (MM) is characterized by uncontrolled proliferation of malignant plasma cells in the bone marrow and peripheral blood. Here, we found that CD40 and CD40L co-expressed on XG1 MM cells and the coordinated expression of CD40-CD40L was critical for production and autocrine IL-6 in XG1 cells. Furthermore, TNF-α enhanced the expression of both CD40 and CD40L expression on XG1 cells. We also found that persistent CD40L/CD40 signaling was required for the constitutive activation of NF-κB in the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Interactions between CD40/CD40L further amplify immune activation and cytokine release, implicating multiple cell types in CRS pathology. Additionally, CD40/CD40L interactions contribute to endothelial cell activation, further elucidating the complex mechanisms underlying CRS [51][52][53].…”
Section: Cytokine-release Syndrome (Crs)mentioning
confidence: 99%
“…Interactions between CD40/CD40L further amplify immune activation and cytokine release, implicating multiple cell types in CRS pathology. Additionally, CD40/CD40L interactions contribute to endothelial cell activation, further elucidating the complex mechanisms underlying CRS [51][52][53].…”
Section: Cytokine-release Syndrome (Crs)mentioning
confidence: 99%
“…Currently, it has been demonstrated that macrophages and monocytes rather than CAR-T cells are the major sources of these cytokines and contribute to CRS (91,92,102,103). In addition, the CD40 and CD40 ligand (CD40L) interactions between CAR-T cells and host antigen-presenting cells (APCs) as well as tumor cells also play an important role in immune activation and the release of cytokines (104)(105)(106). CD40 is expressed on multiple APCs, including B cells, macrophages, dendritic cells (DCs), and monocytes, and highly expressed in a variety of hematological malignancies, such as NHL, AML, MM (105)(106)(107)(108).…”
Section: Cytokine Release Syndromementioning
confidence: 99%
“…In addition, the CD40 and CD40 ligand (CD40L) interactions between CAR-T cells and host antigen-presenting cells (APCs) as well as tumor cells also play an important role in immune activation and the release of cytokines (104)(105)(106). CD40 is expressed on multiple APCs, including B cells, macrophages, dendritic cells (DCs), and monocytes, and highly expressed in a variety of hematological malignancies, such as NHL, AML, MM (105)(106)(107)(108). CD40L is highly expressed on activated T cells, including CAR-T cells (104,109).…”
Section: Cytokine Release Syndromementioning
confidence: 99%
“…Numerous molecules and cytokines can upregulate the secretion of IL-6 derived from BMSCs. It has been previously reported that IL-6 can be detected in the supernatant of MM cells using stimulation with anti-CD40 antibody (69,70). Additionally, IL-1β has also been indicated to be a major cytokine that contributes to the production of BMSC IL-6 via the paracrine loop, which promotes the growth and survival of MM cells (71).…”
Section: The Bone Marrow Microenvironmentmentioning
confidence: 99%